Institutional Development in the Supply Chain System of Oil Palm Agroindustry in South Kalimantan - Hesty Heryani; Agung Cahyo Legowo; Noor Ridha Yanti; Marimin; Sapta Raharja; Machfud; Taufik Djatna; Sri Martini; Taufik Baidawi; Irawan Afrianto (International Journal of Technology, 2022)
Developing oil palm agroindustry in South Kalimantan involves internal and external factors for its sustainability. The long distance of each stakeholder requires a digitally connected system. The research aimed at identifying criteria, sub-criteria, and alternatives in the developed network model, determine the sensitivity to determine the relevance of actor's role, determine the effectiveness and efficiency before and after implementation of the system, and analyse the level of certainty and importance of assumptions developed. The methods used were surveys, focus group discussions, and questionnaires. Experts in the Analytical Network Process (ANP) method were from academia, business, society and government. Supply Chain Operation Reference (SCOR) method to analyse supply chain performance involved 178 respondents. The level of certainty and importance of assumptions was with Strategic Assumption Surfacing and Testing (SAST). The results of the analysis show there was an interdependence between the sub-criteria on the specified criteria and alternatives applied to achieve the goals. Pairwise comparisons showed the highest sub-criteria cluster was the replanting program with a weight of 0.662, for alternative cluster the highest priority weight in the system involving all actors playing a role was 0.391, with relevant sensitivity test results. The results of the analysis of effectiveness and efficiency before and after implementation of the system showed an increase in SCOR value for all actors. The results of SAST analysis were in Quadrant I with the highest level of importance and certainty of 7.6 meaning very important and certain. The implications of the research results can be seen in fostering the use of technology in realizing transparency, especially regarding the price, quality, and traceability of fresh fruit bunches, the realization of a monitoring system for policymakers and capital assistance for independent oil palm smallholders.